Massachusetts emergency departments' resources and physicians' knowledge of management of traumatic dental injuries. Issue 4 (16th July 2012) - Needleman, Howard L.; Stucenski, Keri; Forbes, Peter W.; Chen, Qiaoli; Stack, Anne M.
Abstract: Background: Hospital emergency departments (ED) are confronted with triaging and managing dental emergencies of both traumatic and non‐traumatic origin. However, the literature suggests that there exists inadequate knowledge of the management of traumatic dental injuries (TDI) among medical professionals who must be knowledgeable and have the appropriate resources needed to triage or treat patients presenting with TDI. Aim: The aims of this study were to (i) evaluate the resources of Massachusetts emergency departments (MEDs) for TDI, (ii) determine the knowledge of management of TDI among MED physicians, and (iii) investigate potential factors that affect their knowledge. Materials and methods: Surveys were mailed to MED directors and their physicians. The director survey contained questions regarding institutional information for each emergency department (ED). The physician survey contained questions about physician characteristics and tested their knowledge of managing dental trauma. Results: A total of 72 surveys (16 MED directors and 56 physicians) were returned and included in the analysis. Only 50% of the MEDs had on‐site dental coverage, 43.8% had 24‐h off‐site dental coverage, and none had a formal written dental trauma protocol. MED physician's knowledge of the appropriate management of luxations and avulsions was generally good, but poor for dental fractures. The MED physician's knowledge for the emergent nature of the various injuries was generally good with that of avulsions being the best. Physicians were more likely to have a better knowledge of managing dental trauma if they were specialists in pediatric emergency medicine ( P  =   0.001) or their hospitals had an academic affiliation ( P  =   0.05). Conclusions: Based on the findings from this study, educational campaigns must be undertaken to improve both the resources available to the ED, and the knowledge of physicians regarding emergency management of TDI. In addition, efforts should be made by local dental organizations to provide ED with lists of dentists who are knowledgeable and willing to be available 24 h day −1 to consult with and, if necessary, treat TDI. These efforts would enhance the long‐term outcomes for patients sustaining dental trauma who present to hospital ED.